2021
DOI: 10.1063/5.0055733
|View full text |Cite
|
Sign up to set email alerts
|

A deep learning approach to the forward prediction and inverse design of plasmonic metasurface structural color

Abstract: Mehdi (2021) 'A deep learning approach to the forward prediction and inverse design of plasmonic metasurface structural color.', Applied physics letters., 119 (6).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 31 publications
0
21
0
Order By: Relevance
“…The weights in the inverse network were trained by minimizing the error between the real property input to the tandem network and the output property predicted by the tandem network. Other studies [120][121][122][123] have similarly reported that this strategy helps training convergence, despite the inverse network itself being multivalued, because the training losses are defined only by the property loss and not on the error between the predicted and actual design parameters. The tandem inverse architecture was also found to be effective for simultaneously predicting a combination of discrete design parameters (materials indexed by numbering) and continuous structural parameters (thicknesses) displaying a targeted optical spectrum.…”
Section: Inverse Networkmentioning
confidence: 99%
“…The weights in the inverse network were trained by minimizing the error between the real property input to the tandem network and the output property predicted by the tandem network. Other studies [120][121][122][123] have similarly reported that this strategy helps training convergence, despite the inverse network itself being multivalued, because the training losses are defined only by the property loss and not on the error between the predicted and actual design parameters. The tandem inverse architecture was also found to be effective for simultaneously predicting a combination of discrete design parameters (materials indexed by numbering) and continuous structural parameters (thicknesses) displaying a targeted optical spectrum.…”
Section: Inverse Networkmentioning
confidence: 99%
“…One example is that of localized surface plasmon resonances (LSPRs) which occur when light is trapped between conductive, nanometer-sized features leading to selective resonant absorption and hybridized reflectance modes resulting in intensely saturated, colored metasurface films. Selective coloration can therefore be achieved by engineering unit cell dimensions appropriately [1][2][3] . In this work, we describe a model for inversely obtaining meta-unit geometries to achieve structural color produced 'at will' .…”
Section: Modified Variational Autoencoder For Inversely Predicting Pl...mentioning
confidence: 99%
“…In addition, there are multiple other works using deep learning to efficiently design structural colors in plasmonic and metamaterial structures. [185][186][187] Other practical metasurfaces applications designed by intelligent algorithms include light sails, [188,189] optical information storage (Figure 7D), [162] perfect absorbers, [190] biosensors, [191][192][193][194] and energy conversions. [195] In these metasurface designs, intelligent algorithms perform not only faster, but also more powerful than traditional methods.…”
Section: Intelligent Meta-applicationsmentioning
confidence: 99%
“…In addition, there are multiple other works using deep learning to efficiently design structural colors in plasmonic and metamaterial structures. [ 185–187 ]…”
Section: Design Metastructures With Ai Algorithmsmentioning
confidence: 99%